Comparative Human and Rat "Neurosphere Assay" for Developmental Neurotoxicity Testing. Issue 1 (21st March 2014) - Baumann, Jenny; Barenys, Marta; Gassmann, Kathrin; Fritsche, Ellen
Abstract: The developing nervous system is highly vulnerable to the adverse effects of chemical agents. Currently, there is an increasing need for testing and regulating chemical compounds in general use and, due to the lack of available data, to identify those which are developmental neurotoxicants. In this context, alternative testing strategies are needed in order to allow fast and cost‐efficient screening and to reduce the number of animal experiments usually required. In this unit we present an in vitro three‐dimensional model for developmental neurotoxicity screening based on human and rat neural progenitor cells. This model enables the detection of disturbances in basic processes of brain development, such as proliferation, migration, differentiation and apoptosis, and allows the distinction of these specific disturbances from general cytotoxicity. Furthermore, the comparison of human and rat data provides useful insights into species differences for toxicodynamics of compounds contributing to human risk assessment of developmental neurotoxicants. Curr. Protoc. Toxicol . 59:12.21.1‐12.21.24. © 2014 by John Wiley & Sons, Inc.